Application of machine learning algorithms to predict dead on arrival of broiler chickens raised without antibiotic program - Pranee Pirompud; Panneepa Sivapirunthep; Veerasak Punyapornwithaya; Chanporn Chaosap (My University, 2024)
Understanding the factors of dead-on-arrival (DOA) incidents during pre-slaughter handling is crucial for informed decision-making, improving broiler welfare, and optimizing farm profitability. In this study, three different machine learning (ML) algorithms — Least Absolute Shrinkage and Selection Operator (LASSO), Classification Tree (CT), and Random Forest (RF) - were used together with four sampling techniques to optimize imbalanced data. The dataset comes from 22,115 broiler truckloads from a large producer in Thailand (2021-2022) and includes 14 independent variables covering the rearing, catching, and transportation stages. The study focuses on DOA% in the range of 0.10-1.20%, with a threshold for high DOA% above 0.3%, and records DOA% per truckload during pre-slaughter ante-mortem inspection. With a high DOA rate of 25.2%, the imbalanced dataset prompts the implementation of four methods to tune the imbalance parameters: Random Over Sampling (ROS), Random Under Sampling (RUS), Both Sampling (BOTH), and Synthetic Sampling or Random Over Sampling Example (ROSE). The aim is to improve the performance of the prediction model in classifying and predicting high DOA%. The comparative analysis of the different error metrics shows that RF outperforms the other models in a balanced dataset. In particular, RUS shows a significant improvement in prediction performance across all models compared to the original unbalanced dataset. The identification of the four most important variables for predicting high DOA percentages - mortality and culling rate, rearing stocking density, season, and mean body weight - emphasizes their importance for broiler production. This study provides valuable insights into the prediction of DOA status using an ML approach and contributes to the development of more effective strategies to mitigate high DOA percentages in commercial broiler production.
Keywords: Culling; Lasso; Animal Nutrition and Physiology